The Influence of Online Learning During Pandemic Covid-19 On Students' Learning Interest - Bongguk Haloho; Ulung Napitu (Budapest International Research and Critics University, 2022)
This research uses qualitative research. This qualitative research is descriptive in nature which uses qualitative data analysis so that it becomes easy to understand data exposure. Learning in junior high schools in this study uses online learning or what is commonly called distance learning with the guidance of parents and teachers at school. Students do online learning through Google Classroom, Google Meet, Zoom and interact with teachers through the Whatsapp Group application. This study aims to determine the effect of online learning on students' learning interest in junior high school students during the COVID-19 period. Respondents taken were junior high school students. The results of this study indicate that online learning during the COVID-19 pandemic greatly affects students' interest in learning, students feel bored because they do not meet their friends and teachers directly. Teachers must increase student’s interest in learning and create online learning that makes students’s enthuastic and understand what the teacher is saying. Teachers can arouse student’s interest learning by providing learning motivations and creating interesting learning materials.